Sequential Analysis of the N/O-Glycosylation of Heavily Glycosylated HIV-1 gp120 Using EThcD-sceHCD-MS/MS - Zhang, Yong; Zheng, Shanshan; Zhao, Wanjun; Mao, Yonghong; Cao, Wei; Zeng, Wenjuan; Liu, Yueqiu; Hu, Liqiang; Gong, Meng; Cheng, Jingqiu; Chen, Younan; Yang, Hao (Frontiers in Immunology, 2021)
Deciphering the glycosylation of the viral envelope (Env) glycoprotein is critical for evaluating viral escape from the host’s immune response and developing vaccines and antiviral drugs. However, it is still challenging to precisely decode the site-specific glycosylation characteristics of the highly glycosylated Env proteins, although glycoproteomics have made significant advances in mass spectrometry techniques and data analysis tools. Here, we present a hybrid dissociation technique, EThcD-sceHCD, by combining electron transfer/higher-energy collisional dissociation (EThcD) and stepped collision energy/higher-energy collisional dissociation (sceHCD) into a sequential glycoproteomic workflow. Following this scheme, we characterized site-specific N/O-glycosylation of the human immunodeficiency virus type 1 (HIV-1) Env protein gp120. The EThcD-sceHCD method increased the number of identified glycopeptides when compared with EThcD, while producing more comprehensive fragment ions than sceHCD for site-specific glycosylation analysis, especially for accurate O-glycosite assignment. Finally, eighteen N-glycosites and five O-glycosites with attached glycans were assigned unambiguously from heavily glycosylated gp120. These results indicate that our workflow can achieve improved performance for analysis of the N/O-glycosylation of a highly glycosylated protein containing numerous potential glycosites in one process. Knowledge of the glycosylation landscape of the Env glycoprotein will be useful for understanding of HIV-1 infection and development of vaccines and drugs.